Bedside hyperspectral imaging for the evaluation of microcirculatory alterations in perioperative intensive care medicine: a study protocol for an observational clinical pilot study (HySpI-ICU). Issue 9 (17th September 2020) - Dietrich, Maximilian; Marx, Sebastian; Bruckner, Thomas; Nickel, Felix; Müller-Stich, Beat Peter; Hackert, Thilo; Weigand, Markus A; Uhle, Florian; Brenner, Thorsten; Schmidt, Karsten
Abstract : Introduction: Normalisation of macrocirculatory parameters during resuscitation therapy does not guarantee the restoration of microcirculatory perfusion in critical illness due to haemodynamic incoherence. Persistent microcirculatory abnormalities are associated with severity of organ dysfunction and mandate the development of bedside microcirculatory monitoring. A novel hyperspectral imaging (HSI) system can visualise changes in skin perfusion, oxygenation and water content at the bedside. We aim to evaluate the effectiveness of HSI for bedside monitoring of skin microcirculation and the association of HSI parameters with organ dysfunction in patients with sepsis and major abdominal surgery. Methods and analysis: Three independent groups will be assessed and separately analysed within a clinical prospective observational study: (1) 25 patients with sepsis or septic shock (according to sepsis-3 criteria), (2) 25 patients undergoing pancreatic surgery and (3) 25 healthy controls. Patients with sepsis and patients undergoing pancreatic surgery will receive standard therapy according to local protocols derived from international guidelines. In addition, cardiac output of perioperative patients and patients with sepsis will be measured. Healthy controls undergo one standardised evaluation. The TIVITA Tissue System is a novel HSI system that uses the visible and near-infrared spectral light region to determine tissue microcirculatory parameters. HSI analysis (hand/knee) will be done in parallel to haemodynamic monitoring within defined intervals during a 72-hour observation period. HSI data will be correlated with the Sequential Organ Failure Assessment score, global haemodynamics, inflammation and glycocalyx markers, surgical complications and 30-day outcome. Ethics and dissemination: The protocol has been approved by the local ethics committee of the University of Heidelberg (S-148/2019). Study results will be submitted to peer-reviewed journals and medical conferences. Trial registration number: DRKS00017313; Pre-results.